HOW IS THE DISPUTE RESOLUTION MECHANISM IN INTERNATIONAL BUSINESS LAW? - Asep Sapsudin (SEAN Institute, 2023)
Alternative dispute resolution exists as a dispute resolution mechanism that offers advantages or advantages compared to dispute resolution through court mechanisms. Currently, international business activities are increasingly complex, and there are also many potential disputes between business people. Therefore, the existence of a dispute resolution mechanism is important to provide, especially a more effective and efficient dispute resolution mechanism. Rivalry or competition that is increasing and intense between these countries often creates conflicts and disputes that must be resolved immediately, but the resolution of these disputes must pay attention to the structure and nature of the international community and the different national communities. The handling of international disputes that are in the hands of each country is also reflected in the arrangements for handling disputes in the General Agreement on Tariffs and Trade (GATT) which was a joint agreement of each of its member countries before the World Trade Organization (WTO) was formed. As for the study of the field of dispute resolution law, dispute resolution mechanisms that are considered more effective and efficient usually refer to the concept of Alternative Dispute Resolution (Alternative Dispute Resolution).